Detection of Del Phenotype in RHD-negative blood using heat elution technique and sequence specific primerpolymerase chain reaction / Nor Elizatul Izzati Maswan - Maswan, Nor Elizatul Izzati (2015)
DEL is the weakest RhD-positive phenotype that commonly mistyped as RhDnegative. It may induce alloimmunization when transfused to RhD-negative recipients. Serologically, it can only be detected via adsorption-elution test. In Malaysia, few data exist regarding DEL phenotype. The objective of this study was to detect DEL phenotype in RhD-negative blood using adsorption-elution technique and Sequence Specific Primer-Polymerase Chain Reaction (SSP-PCR). A total of 43 RhD-negative blood samples were collected from Pusat Darah Negara. Rh phenotype for each sample was tested. Heat elution by incubation at 56°C for 10 minutes were implemented. Indirect Antiglobulin Test against Rh(+) cells and Rh(-) cells were completed on the eluates and last wash supernatant. Then, identification of DEL carrying RHD1227A was performed via SSP-PCR. Rh-phenotype identified were ccee with 79.07%, Ccee with 13.95%,4.65% of ccEe phenotype and CCee phenotype with only 2.33%. One (2.33%) out of 43 samples was identified as DEL phenotype carrying RHDI227A allele when tested using SSP-PCR but none was identified from adsorption-elution. SSP-PCR was more sensitive and specific compared to adsorption-elution test. Hence, implementation of SSP-PCR for efficient DEL phenotypes typing is highly recommended.